1983
DOI: 10.1002/bbpc.19830870805
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Reactions of OH‐Radicals with Benzene, Benzene‐d6 and Naphthalene

Abstract: Absolute rate constants for the reactions of hydroxyl radicals with benzene (1), benzene‐d6 (2), and naphthalene (3) have been obtained using excimer laser photolysis to generate OH and time resolved resonance fluorescence as its monitor. Reaction (1) was studied at total pressures between 1.5 and 112 mbar at 298 K using Ar as a diluent gas. k1 is found to increase with pressure up to –40 mbar, but to be essentially pressure independent at still higher pressures, k 1∞ (298 K) = (7.0 ± 1.5) 1011 cm3/mol · s. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
89
2
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 16 publications
15
89
2
1
Order By: Relevance
“…In air (chloro)benzene, by itself, did not measurably react below 750 K, but in the presence of small proportions of .OH radical forming agents, including aliphatic hydrocarbons such as cyclohexane [6] or cyclohexadiene 171 undergoing slow combustion, phenolic products were obtained from a variety of benzene derivatives. Substitution patterns of ZC,H,OH from C&Z, as well as substrate selectivities were found to vary with temperature, clearly indicating a mechanistic change, under our conditions, around 650 K. A t increasing temperature, phenol formation appears to shift from a .OH addition pathway to one involving H-abstraction by .OH, a finding consonant with those based on -OH reaction rates with benzene [8,9]. Thermokinetic analysis [6] supported this interpretation and it was also shown that, at still higher temperatures, addition of O(3P) to arene could increase in importance as a pathway to phenol.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…In air (chloro)benzene, by itself, did not measurably react below 750 K, but in the presence of small proportions of .OH radical forming agents, including aliphatic hydrocarbons such as cyclohexane [6] or cyclohexadiene 171 undergoing slow combustion, phenolic products were obtained from a variety of benzene derivatives. Substitution patterns of ZC,H,OH from C&Z, as well as substrate selectivities were found to vary with temperature, clearly indicating a mechanistic change, under our conditions, around 650 K. A t increasing temperature, phenol formation appears to shift from a .OH addition pathway to one involving H-abstraction by .OH, a finding consonant with those based on -OH reaction rates with benzene [8,9]. Thermokinetic analysis [6] supported this interpretation and it was also shown that, at still higher temperatures, addition of O(3P) to arene could increase in importance as a pathway to phenol.…”
Section: Introductionsupporting
confidence: 80%
“…Due to its reversibility [8,9], addition (step 3) cannot effectively compete with reactions (1) and (21, (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…10. stant for the analogous decomposition of the OH-naphthalene adduct Alternatively, the rate constant k-3 can be estimated from the rate conand the thermochemistries of reactions (-3) and (6). Assuming that the resonance stabilization energy of the Nos-aromatic adduct is identical to that for the OH-aromatic adduct, the NO3-aromatic adduct is 10.9 kcal mol-' less stable towards thermal decomposition than is the OH-aromatic adduct [42] observed that the OH-naphthalene adduct was thermally more stable than the hydroxycyclohexadienyl radical by 3.8 kcal mo1-l (assuming a n identical pre-exponential factor), then the decomposition rate of the OH- The observation of Lorenz and Zellner [42] that the OH-naphthalene adduct is more stable towards thermal decomposition than the OH-benzene adduct by 3.8 kcal mol-' suggests that the NO3-naphthalene-adduct may also be correspondingly more stable towards thermal decomposition than the NO3-benzene adduct. If so, the rate constant for thermal decomposition of the NO3-benzene adduct is ca.…”
Section: Resultsmentioning
confidence: 99%
“…[37] The reactions of O and OH with benzene and substituted benzenes have also been studied. [38] The presence of partially oxidized higher aromatic species in fuelrich flames has also led to knowledge of the first intermediates of oxidative attack. [31] This leads to the following general picture, in particular with respect to the effects on the growth reactions.…”
Section: The Role Of Oxidation Reactions In Pah Growthmentioning
confidence: 99%